Effect of organic fertilisers on the yield and quality of cocoa (Theobroma cacao L.) grown on a vertisol - Boney Muda (2019)
The use of fertiliser particularly for the inorganic fertilisers has increased annually to cope the global demand of crop production. Nevertheless, inorganic fertiliser is expensive and associated with the negative effects to the environment and soil health. Alternatively, organic materials can be composted and used as fertiliser. Although organic fertilisers have low nutrient concentration and solubility, organic fertilisers release nutrients slowly which makes them available for a longer period. Moreover, the waste by-products such as biomass and manure from plantation and livestock farms are available in abundance. By adopting proper composting methods, these abundant wastes can be optimally used particularly in cocoa plantation. This study was conducted at Field 21 (F21) of Malaysian Cocoa Board Research and Development Centre in Madai Kunak, Sabah for 27 months duration. The objective was to determine the effects of different types of fertilisers (T1 – Inorganic Fertiliser (control), T2 – Chicken Manure, T3 – Cow Manure, T4 – Empty Fruit Bunch, and T5 – Cocoa Pod Husk) and their frequency application (F1 – Every 4-months, and F2 – Every 2-Months). Design for the trial was Random Complete Block Design (RCBD) in 3 replicates with total of 30 experimental plots. The parameters were studied in three stages; pre-harvest (pod and bean analyses, production of cocoa, and soil and leaf sampling for chemical analyses), postharvest processing (sugar and fat content, pH and titratable acidity analyses) and chocolate production. In addition, cost benefit analysis was also conducted for a comparative economic cost between the fertilisers. The results showed that there were no significant differences on the pod and bean quality, bean chemical characteristics, crop production, flavour attributes, soil chemical properties and leaf nutrient content between inorganic and organic fertilisers regardless of the frequency of application. However, the organic fertilisers significantly reduced bean acidity up to 90.9% compared to inorganic fertilisers which resulted in better chocolate flavour. Lastly, this study indicated that empty fruit bunch and cow manure treatment for every 4-months and 2-months application, respectively is the best treatments in providing the highest net income based on the cost benefit analysis compared to inorganic fertiliser treatment. Therefore, this study has clearly demonstrated that organic fertilisers were determined to be alternative to inorganic fertiliser and they are environmental-friendly.